Response of Lyapunov exponents to diffusion state of biological networks - Altuntas, Volkan; Gok, Murat; Kocal, Osman Hilmi (Zielona Góra: Uniwersytet Zielonogórski)
The topologies of protein-protein interaction networks are uncertain and noisy. The network topology determines the reliability of computational knowledge acquired from noisy networks and can impose the deterministic and non-deterministic character of the resulting data. In this study, we analyze the effect of the network topology on Lyapunov exponents and its relationship with network stability.
Keywords: synthetic networks; biological networks; diffusion; stability; Lyapunov exponents